Facts about Carbohydrate - Nancy J. Gal; Amanda L. Ford; Wendy J. Dahl (EDIS, 2014)
Carbohydrate, fat, and protein are the three nutrients that provide energy (calories). However, carbohydrate from starch and sugars is our main and most important source of energy. During digestion, starch is broken down to sugar (glucose). Carbohydrate in the form of glucose provides energy to cells, tissues, and organs to carry out daily activities. Some glucose is stored in the liver and muscle cells for later use when required. Children need carbohydrate for growth, and adults need carbohydrate to maintain their weight. This 3-page fact sheet was written by Nancy J. Gal, Amanda L. Ford, and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, February 2014.